Challenges and opportunities of remote public involvement and community engagement during a pandemic: refining the MapMe childhood healthy weight intervention. (July 2022) - McSweeney, L; Arnott, B; Jones, A; Cain, G; Jenkins, J; Andras, A; Adamson, A
Aims: Including parents and other stakeholders in the development of interventions to address the sensitive public health issues such as childhood obesity, through public involvement is critical. However, the Covid-19 pandemic has created a challenge for public involvement and engagement activities (PICE). The aim of this paper is to describe the process and challenges of setting up, maintaining, evaluating, and recording impact of three public and stakeholder groups via remote methods in the context of the MapMe2 study during the Covid-19 pandemic. Parental reaction to result letters received as part of the National Child Measurement Programme (NCMP) informing parents of their child's overweight status is often one of hostility or disbelief. As a result, parents often do not act on these letters to address child overweight. The MapMe2 study is working in collaboration with the NCMP and local authorities, building on previous work (MapMe) and aims to support parents of primary school–aged children to recognise and maintain a healthy weight in their child. The existing MapMe Intervention includes an enhanced NCMP child weight result letter, supplemented with Body Image Scales (BIS), and an intervention website with material to support healthy eating, physical activity, and signposting supporting information. The intervention was to be refined and the evaluation informed with PICE input. Methods: Covid-19 restrictions meant that planned face-to-face PICE methods had to be altered with all recruitment, all correspondence, and activities taking place remotely. A Parent Involvement Panel (PIP), a child panel, and an expert panel were established. Several adaptations were made to accommodate a new way of involving the public in research. Results/Conclusions: Working remotely created many challenges and was a learning experience for all involved. However, an active group was successfully established. Using continuous assessment and evaluation methods, we were able to demonstrate successful involvement and engagement in the refinement of the MapMe2 study. Through the sharing of PICE methods practice, this paper adds to the literature, the value of partnership working.